PENGARUH BRAND IMAGE DAN CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP CUSTOMER SATISFACTION DALAM MENINGKATKAN REPETITIVE BUYING PADA SALON JOHNNY ANDREAN MALL SKA PEKANBARU - Trisia Lika; Sri Restuti; Tengku Firli Musfar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research to know the effect of Brand Image and Customer Relationship Management to Customer Satisfaction in improving Repetitive Buying. In this study, there are four variables : brand image (X1), customer relationship management (X2), customer satisfaction (Y1), and repetitive buying (Y2). Population and sample in this research is all customers Salon Johnny Andrean Mall Ska Pekanbaru, with a sample of 100 respondents were selected by using purposive sampling method with criteria used is the Salon Johnny Andrean Mall Ska Pekanbaru at least 2 times. Collecting data in this study with questionnaire method. To analyze the data in this study using path analysis with program SPSS for Windows Version 21. The results showed that : 1) the brand image have a positive influence and significant impact to customer satisfaction with path coefficient 0,572, 2) the brand image have a positive influence and significant impact to repetitive buying with path coefficient 0,234, 3) the customer relationship management have a positive influence and significant impact to customer satisfaction with path coefficient 0,355, 4) the customer relationship management have a positive influence and significant impact to repetitive buying with path coefficient 0,224, 5) the customer satisfaction have a positive influence and significant impact to repetitive buying with path coefficient 0,292.Keywords : Brand Image, Customer Relationship Management, Customer Satisfaction, and Repetitive Buying.